1973
DOI: 10.1002/bjs.1800601015
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal complications of radiotherapy

Abstract: The clinical features of 38 patients with intestinal complications after radiotherapy are recorded. Intestinal complications are commonly progressive and in this series led to the death of 14 patients (37 per cent). Nine of these patients had no sign of recurrent tumour. ‘Spontaneous’ necrosis of the irradiated bowel and necrosis of intestinal anastomoses after surgical operation carried a particularly high mortality. Only 3 patients (8 per cent) became completely asymptomatic after treatment of their bowel di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
7

Year Published

1975
1975
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 6 publications
(4 reference statements)
0
16
0
7
Order By: Relevance
“…The follow-up period in this study is short and further complications are still to be expected, although more than 90% occur within two years of treatment (Wellwood & Jackson 1973). In this series of 200 patients, approximately half received intracavitary Cathetron treatment alone and none of these suffered any bowel injury.…”
Section: Discussionmentioning
confidence: 82%
“…The follow-up period in this study is short and further complications are still to be expected, although more than 90% occur within two years of treatment (Wellwood & Jackson 1973). In this series of 200 patients, approximately half received intracavitary Cathetron treatment alone and none of these suffered any bowel injury.…”
Section: Discussionmentioning
confidence: 82%
“…Wellwood and Jackson [13] reported well-developed arterial sclerosis and an increase in the amount and density of fibrous tissue in the intestinal and colonic submucosa in patients who received abdominal irradiation for different reasons. Experimentally, an early and persistent reduction in colorectal anastomotic blood flow was found in pigs after preoperative radiation therapy with a total dose of 4,250 cGy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that preoperative hyperfractionated RT with a total dose of 41.6 Gy did not affect the strength of colonic anastomosis in rats provided that one limb only of the anastomosis was irradiated [12]. Several studies, clinical and experimental, have reported histological changes in the small intestine and colon after RT [13][14][15][16]. Animal studies investigating the influence of combined RCT on colonic anastomosis have yielded conflicting results [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Sie geht mit Schmerzen, Tenesmen, Durchfiillen und gelegentlich auch Blutungen einher. Solche Friihreaktionen klingen meist innerhalb einiger Wochen ab und erfordern in der Regel keine chirurgische Behandlung [16,19].…”
Section: S Tr Ahl Enr E Ak T Io Nenunclassified